Low density hot rolled steel, its manufacturing method and use of such steel for manufacturing vehicle parts
A tailored steel composition and microstructure address the limitations of existing low density steels by balancing strength, hardness, and ductility, enabling efficient weight reduction in vehicle parts through controlled alloying and microstructural design.
Patent Information
- Application Number
- JP2024534249
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2025-01-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing low density steels do not effectively balance mechanical strength, hardness, and ductility, limiting their use in vehicle parts due to issues like stiffness reduction and acoustic problems, while alternative steels with added aluminum lack hardness and are prone to brittleness.
A steel composition with specific alloying elements (C, Mn, Al, Si, S, P, N, Nb, Ti, Cu, Ni, Mo, Cr, Ca, Ce, B, Mg, Zr, Sb, Sn) and microstructure (55-80% ferrite, 15-50% austenite, 0-10% martensite) achieving a relative density <7.3 and nanohardness distribution of <4 GPa for 45-50% and <5 GPa for 20-22%, avoiding brittle phases like bainite and kappa.
The solution provides a steel with balanced mechanical properties, enabling efficient weight reduction in vehicle parts without compromising stiffness, ductility, and hardness, suitable for various manufacturing processes.
Smart Images

Figure 2025500790000001 
Figure 2025500790000002 
Figure 2025500790000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a low density steel. The steel according to the invention is particularly suitable for the manufacture of parts for vehicles, such as land vehicles, or for further processing to produce cold rolled steel sheets and then vehicle parts. [Background technology]
[0002] Environmental regulations force car manufacturers to continuously reduce the CO2 emissions of their vehicles. To do so, they have several options, the main ones being to reduce the weight of the vehicle or to increase the efficiency of the engine system. Improvements are often achieved by combining the two approaches. The present invention concerns the first option, i.e. reducing the weight of the car. Indeed, in this particular field, there are two methods:
[0003] The first method consists of decreasing the thickness of the steel while increasing its level of mechanical strength. Unfortunately, this solution has limitations due to the significant decrease in stiffness of certain automotive components and the appearance of acoustic problems that can cause discomfort for the passengers, not to mention the inevitable decrease in ductility associated with the increase in mechanical strength.
[0004] The second method consists of reducing the density of steel by alloying it with other, lighter metals such as aluminum. Among these types of steel, low density steels can significantly reduce the weight of hot-rolled steels while having attractive mechanical and physical properties. In particular, US2003 / 0145911 discloses Fe-Al-Mn-Si light steels with good formability and high strength. However, the steels of US2003 / 0145911 do not demonstrate the hardness of low density steels, which is an important property for processing steels, and therefore the steels cannot fully take advantage of their low density for parts of any shape. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] US Patent Application Publication No. 2003 / 0145911 Summary of the Invention [Problem to be solved by the invention]
[0006] It is therefore an object of the present invention to provide a steel sheet presenting a relative density of less than 7.3, a steel hardness of less than 280 Hv, in which more than 45% of the microstructural grains have a nanohardness of less than 4 GPa and less than 22% of the microstructural grains have a nanohardness of more than 5 GPa. [Means for solving the problem]
[0007] Therefore, in a preferred embodiment of the present invention, a steel sheet is provided which presents a relative density of 7.2 or less, a steel hardness of less than 275 Hv, in which more than 50% of the microstructural grains have a nanohardness of less than 4 GPa and less than 20% of the microstructural grains have a nanohardness of more than 5 GPa. Other features and advantages of the present invention will become apparent from the following detailed description of the invention.
[0008] The carbon content is 0.12% to 0.25% by weight, more preferably 0.13% to 0.2% by weight. Carbon is a gamma-generating element that plays an important role in the formation of retained austenite and also imparts strength and ductility. The carbon content is advantageously 0.13% to 0.2% in order to simultaneously obtain high strength, elongation and stretch flangeability.
[0009] The manganese content is present in the range of 3% to 10% by weight. Manganese is an important alloying element in this system, mainly because alloying with very high amounts of manganese stabilizes the austenite up to room temperature. This helps to achieve target properties such as elongation and yield strength. Manganese, together with carbon, controls the formation of carbides at grain boundaries at high temperatures, thereby controlling high temperature brittleness. If manganese is present in excess of 10%, it may result in central segregation that is detrimental to the ductility of the steel of the present invention. Manganese does not stabilize the austenite in sufficient amounts at room temperature if present at less than 3%. The preferred limits for the presence of manganese are 4% to 9%, more preferably 4% to 8%.
[0010] The aluminum content is present between 3.5% and 6.5% by weight. The addition of aluminum to the steel of the present invention effectively reduces its density. Aluminum is an alpha generating element and therefore tends to promote the formation of ferrite, especially delta ferrite. Aluminum has a relative density of 2.7, which affects the mechanical properties. As the aluminum content increases, the uniform elongation decreases due to the reduction in dislocation mobility, but the mechanical strength and elastic limit also increase. Below 3.5%, the density reduction due to the presence of aluminum becomes less beneficial. Above 6.5%, the presence of ferrite increases beyond expected limits, adversely affecting the present invention. Furthermore, the presence of Al above 6.5% may form intermetallic compounds such as Fe-Al, Fe3-Al and other (Fe,Mn)Al intermetallic compounds, which impart brittleness to the product that may cause cracking of the steel during cold rolling and may be detrimental to the toughness of the steel. Preferably, the aluminum content is restricted strictly to less than 6.5% in order to prevent the formation of brittle intermetallic precipitates, the preferred limits therefore being between 4% and 6%, more preferably between 5% and 6%.
[0011] Silicon is an optional element that allows the density of the steel to be reduced and is effective for solid solution hardening. Nevertheless, its content is limited to 2% by weight, since above that level this element has a tendency to form strong adhesive oxides that cause surface defects. The presence of surface oxides can impair the wettability of the steel and cause defects during potential hot-dip galvanizing operations. Therefore, the Si content is preferably limited to less than 1.5%.
[0012] Sulfur and phosphorus are grain boundary embrittling impurities whose respective contents must not exceed 0.03% and 0.1% by weight in order to maintain sufficient hot ductility.
[0013] The nitrogen content must be less than 0.1% by weight to prevent the precipitation of AlN and the formation of volumetric defects (blisters) during solidification.
[0014] Niobium may be added as an optional element in the steel of the present invention in an amount of 0.01% to 0.03% by weight to provide grain refinement, which allows a good balance between strength and elongation to be obtained. However, niobium tends to retard recrystallization during hot rolling and annealing, so the limit is kept to 0.03%.
[0015] Titanium, like niobium, may be added as an optional element to the steel of the present invention in amounts of 0.01% to 0.2% by weight for grain refinement.
[0016] Copper may be added as an optional element in an amount of 0.01% to 2.0% by weight to increase the strength of the steel and improve its corrosion resistance. A minimum of 0.01% is required to obtain such effects. However, if the content exceeds 2.0%, it may deteriorate the surface appearance.
[0017] Nickel may be added as an optional element in an amount of 0.01-3.0% by weight to increase the strength of the steel and improve its toughness. A minimum of 0.01% is required to obtain such an effect. However, if its content exceeds 3.0%, nickel causes a decrease in ductility.
[0018] Molybdenum can be added as an optional element present in the steel of the present invention in the range of 0% to 0.5% by weight. When added in an amount of at least 0.01%, molybdenum plays an effective role in improving hardenability and hardness. Mo is also beneficial for the toughness of hot rolled products, resulting in easier manufacturing. However, the addition of molybdenum excessively increases the cost of adding alloying elements, so for economic reasons its content is limited to 0.5%. The preferred limit for molybdenum is 0% to 0.4%, more preferably 0% to 0.3%.
[0019] Chromium may be added as an optional element to the steel of the present invention in an amount between 0% and 0.6% by weight. Chromium provides strength and hardening to the steel, but if used in excess of 0.5% it will damage the surface finish of the steel. The preferred limits for chromium are 0.01% to 0.5%, more preferably 0.01% to 0.2%.
[0020] Other elements such as calcium, cerium, boron, magnesium or zirconium can be added individually or in combination in the following weight proportions: Ce≦0.1%, B≦0.01, Ca≦0.005, Mg≦0.005 and Zr≦0.005. Up to the maximum content levels indicated, these elements make it possible to refine the ferrite particles during solidification.
[0021] Furthermore, some trace elements such as Sb, Sn, etc. may result from the processing of the steel. The maximum limit at which these elements are tolerated and are not detrimental to the steel of the invention is 0.05% by weight, either cumulatively or alone, and it is preferred that the steel of the invention has a content of these elements as low as possible, preferably less than 0.03%.
[0022] The microstructure of the steel plate according to the present invention contains, in area fraction, 55% to 80% ferrite, 15% to 50% austenite, and 0% to 10% martensite.
[0023] The ferrite matrix is present as the main phase of the steel of the present invention and is present in the steel of the present invention at an area fraction of 55% to 80%, preferably at an area fraction of 58% to 80%, more preferably at an area fraction of 58% to 78%. The ferrite is formed during the solidification of the slab from liquid iron and during the cooling after hot rolling, the ferrite of the present invention is preferably formed as a banded structure having an average band thickness of 1 micron to 70 microns, more preferably 1 micron to 65 microns, more preferably 2 microns to 62 microns. The presence of the ferrite matrix in the present invention gives strength to the steel. However, the presence of the ferrite content in the present invention may have a negative effect because the solubility of carbon in ferrite increases with increasing temperature when it exceeds 80%. However, carbon in solid solution is very brittle for low density steels, since it reduces the mobility of dislocations, which is already low due to the presence of aluminum. Therefore, the balance between the ferrite content and austenite is very important in giving the required mechanical properties to the present invention.
[0024] Austenite is an essential minor component of the steel of the present invention and is present at 15-50%, the austenite of the present invention preferably having an average grain size of 2 microns to 25 microns, more preferably 2 microns to 22 microns. Austenite is known to have a higher solubility of carbon than ferrite and acts as an effective carbon trap. Austenite present at levels above 50% adversely affects the present invention by impairing the formation of ferrite and thereby impairing the desired properties of the steel of the present invention. Thus, the preferred limits of austenite presence are 15% to 45%, more preferably 18% to 45%.
[0025] Martensite is an optional component of the steel of the present invention, present in the area fraction of 0% to 10% of the microstructure. Martensite according to the present invention is formed after coiling, especially during cooling below the Ms temperature, and imparts ductility and strength to such steel. Preferably, the content of martensite is 0% to 8%, more preferably 0% to 6%.
[0026] In addition to the above microstructures, the microstructure of low density hot rolled steel does not contain microstructural constituents such as bainite and kappa precipitates.
[0027] More than 45% of the grains in the microstructure of the steel have a nano-hardness of less than 4 GPa, this feature of the steel of the invention facilitates further processing of the hot rolled steel for various manufacturing processes such as cold rolling, extrusion, pressing, stamping, hydroforming, hemming, punching and drawing. By keeping the nano-hardness of more than 45% of the grains in the microstructure below 4 GPa, the steel of the invention ensures that the hot rolled steel is not too hard for manufacturing processes, while at the same time the steel is not too soft for mechanical properties. The preferred limit of grains with a nano-hardness of less than 4 GPa is greater than 50%, more preferably 55%.
[0028] In addition to the above, the hot rolled steel of the present invention also limits the presence of grains in the microstructure of the steel with a nanohardness of more than 5 GPa and not more than 22%. This is because whenever there are more than 22% grains with a nanohardness of 5 GPa, they cause excessive wear on the industrial machines used to manufacture parts for the automotive industry, and for example, when the steel contains more than 22% grains in the microstructure with a nanohardness of 5 GPa or more, it is impossible to carry out cold rolling without any prior heat treatment. Therefore, it is preferable that the grains with a nanohardness of 5 GPa or more are less than 20%, more preferably less than 18%.
[0029] In addition to the above microstructure, the microstructure of hot rolled low density steel is free of minor constituents such as kappa precipitates and bainite.
[0030] The steel sheet according to the invention can be manufactured by any suitable manufacturing method, which the person skilled in the art can define. However, it is preferred to use the method according to the invention, which comprises the following steps: The steel plate according to the invention is preferably produced by a process in which a semi-finished product such as a slab, thin slab or strip made of the steel according to the invention having the above mentioned composition is cast and the cast input stock is first cooled to room temperature and then reheated to a temperature above 1000° C., preferably above 1150° C., more preferably above 1200° C., or the cast semi-finished product can be used directly at such temperatures without intermediate cooling. The semi-finished product of this process is considered as a slab.
[0031] The reheated slab then undergoes hot rolling. The hot rolling finish temperature must be at least 750°C, preferably at least 770°C. The hot rolling finish is held above 750°C to ensure that the hot rolling must be completed in areas with 50% to 100% delta ferrite.
[0032] The hot rolled strip thus obtained is then cooled, said cooling being started immediately after the end of hot rolling, the hot rolled strip being cooled from the end of hot rolling to a coiling temperature range of 380°C to 480°C at a cooling rate CR1 of 10°C / s to 150°C / s. In a preferred embodiment, the cooling rate CR1 is between 20°C / s and 120°C / s, more preferably the cooling rate CR1 is between 30°C / s and 100°C / s. During this cooling, the steel of the present invention starts to transform from delta ferrite to ferrite and austenite.
[0033] The hot rolled steel must then be coiled at a temperature of 380°C to 480°C, preferably the coiling is carried out at 390°C to 470°C, more preferably the coiling is carried out at 400°C to 460°C.
[0034] The hot rolled steel is cooled from the coiling temperature to room temperature at a cooling rate CR2 of 1° C. / h to 50° C. / h. In a preferred embodiment, the cooling rate CR2 is 10° C. / h to 40° C. / h to obtain a low density hot rolled steel.
[0035] Thereafter, an optional pickling or any other descaling step may be performed to facilitate further processing, such as cold rolling, cutting into sheet piles, forming, etc., to manufacture the hot rolled steel into vehicle parts.
[0036] After cooling to room temperature, the hot-rolled steel may optionally be subjected to a metal coating operation to improve its protection against corrosion. The coating process used may be any process compatible with the steel of the invention. Mention may be made of electrolytic or physical vapor deposition, with particular emphasis on jet deposition. The metal coating may be based, for example, on zinc or aluminum.
[0037] Preferably, the aluminum-based coating contains less than 15% Si, less than 5.0% Fe, optionally 0.1% to 8.0% Mg and optionally 0.1% to 30.0% Zn, the balance being Al.
[0038] Advantageously, the zinc-based coating comprises 0.01-8.0% Al, optionally 0.2-8.0% Mg, the balance being Zn. EXAMPLES
[0039] The following studies, examples, schematic illustrations and tables presented herein are non-limiting in nature and should be considered for illustrative purposes only, illustrating advantageous features of the present invention.
[0040] The steel sheets manufactured with steels having different compositions are summarized in Table 1, the presence of phosphorus is always less than 100 ppm for all steels, respectively, manufactured according to the process parameters specified in Table 2. Then, Table 3 summarizes the microstructures of the steel sheets obtained during the tests and Table 4 summarizes the evaluation results of the properties obtained.
[0041] Table 1 - Composition Table 1
[0042] [Table 1] Underlined values: not according to the invention.
[0043] Table 2 - Process parameters The steel of the invention and the reference steel are reheated at 1200°C.
[0044] [Table 2]
[0045] The obtained samples were then analyzed and the corresponding microstructural elements and mechanical properties were summarized in Tables 3 and 4, respectively.
[0046] Table 3 summarizes the results of tests carried out according to the standards with XRD and various microscopes such as optical and scanning electron microscopes to determine the microstructural composition of both the steel of the invention and the reference test. The austenite fraction was measured by XRD. The area fractions of kappa carbides and martensite were determined by optical and scanning electron microscopy through the analysis of at least four images. The area fraction of ferrite was calculated by subtracting the sum of the fractions of all other phases to 100%.
[0047] Table 3
[0048] [Table 3] I=according to the invention, R=reference, underlined values: not according to the invention.
[0049] From the above table it can be seen that all tests according to the present invention meet the microstructure targets.
[0050] Table 4 summarizes the mechanical and surface properties of both the steels of the invention and the reference steel.
[0051] Table 4: Mechanical properties of the test Hardness is measured by the Vickers hardness test, performed according to the ISO 6507 standard. To determine the relative density of steel, the volume of a steel sample is measured by gas displacement pycnometry using helium on one side and its corresponding mass is measured on the other side. It is then expressed in g / cm 3 Calculate the mass ratio per volume of the unit steel, 1g / cm 3 It can be further divided by the mass ratio per volume of water at 4 °C, which reaches . The resulting value is unitless and is the relative density of steel. To determine the nanoindentation, the samples are prepared by OPU polishing (8 min, diluted to 50%) before performing the nanoindentation test with a load of 3 mN. A spacing of 8 μm between the points of the indentation grid is chosen.
[0052] [Table 4] I=according to the invention, R=reference, underlined values: not according to the invention.
[0053] The examples show that the steel sheets according to the invention are unique in that they exhibit all the targeted properties thanks to their specific composition and microstructure.
Claims
1. A low density hot rolled steel, comprising, by weight: 0.12%≦carbon≦0.25%, 3%≦Manganese≦10%, 3.5%≦Aluminum≦6.5%, 0%≦phosphorus≦0.1%, 0%≦sulfur≦0.03%, 0%≦nitrogen≦0.1%, and optionally one or more of the following elements: 0%≦silicon≦2%; 0.01%≦niobium≦0.03%, 0.01%≦Titanium≦0.2%, 0%≦molybdenum≦0.5%, 0%≦chromium≦0.6%, 0.01%≦copper≦2.0%, 0.01%≦Nickel≦3.0%, 0%≦Calcium≦0.005%, 0%≦boron≦0.01%, 0%≦Magnesium≦0.005%, 0%≦zirconium≦0.005%, 0%≦cerium≦0.1%, Including, A low density hot rolled steel, the balance of which is iron and unavoidable impurities, the steel plate having a microstructure comprising, by area fraction, 55% to 80% ferrite, 15% to 50% austenite and 0% to 10% martensite, the microstructure having a nano-hardness of less than 4 GPa must account for more than 45% of the grains, and the microstructure having a nano-hardness of more than 5 GPa must account for less than 22% of the grains.
2. 2. The steel according to claim 1, wherein the carbon content is comprised between 0.13% and 0.2%.
3. 3. The steel according to claim 1 or 2, wherein the content of manganese is comprised between 4% and 9%.
4. A steel according to any one of the preceding claims, in which the content of martensite is between 0% and 8%.
5. A steel according to any one of the preceding claims, in which the content of retained austenite is between 15% and 45%.
6. A steel according to any one of the preceding claims, in which the content of ferrite is between 58% and 80%.
7. The steel sheet according to any one of claims 1 to 6, wherein the steel sheet is coated with a metallic coating.
8. 1. A method for producing low density hot rolled steel, comprising the steps of: Providing a slab whose composition is in accordance with claims 1 to 3; reheating the slab to a temperature above 1000°C and hot rolling it to a final rolling temperature of at least 750°C; Cooling the hot-rolled steel from the finish of hot rolling to a coiling temperature range of 380°C to 480°C at a cooling rate CR1 of 10°C / s to 150°C / s; The hot-rolled steel is then coiled at a temperature of 620°C to 740°C; The hot-rolled steel is then cooled from the coiling temperature to room temperature at a cooling rate CR2 of 1° C. / h to 50° C. / h to obtain a low-density hot-rolled steel. method.
9. 9. The method of claim 8, wherein the final rolling temperature is 770°C or higher.
10. The method according to any one of claims 8 and 9, wherein the coiling temperature is comprised between 390°C and 470°C.
11. The method according to any one of claims 8 to 10, further comprising a final coating step.
12. Use of a steel sheet according to any one of claims 1 to 7 or obtained according to the method according to any one of claims 8 to 11 for manufacturing structural or safety and other parts of a vehicle.
Citation Information
Patent Citations
Compound micro-alloying medium manganese steel for automobiles and manufacturing method thereof
CN108866435A
Cold-rolled steel sheet, manufacturing method, and vehicle
JP2016529392A
Cold-rolled and heat-treated steel sheet, its manufacturing method and use of such steel for the manufacture of vehicle parts
JP2021507110A
Low density high strength steel and method for producing said steel
US20140363694A1
Highly stable, steel and steel strips or steel sheets cold-formed, method for the production of steel strips and uses of said steel
US20030145911A1